OPTIMIZATION OF EXPERIMENTAL METHOD FOR HORIZONTAL ROOFING STRUCTURES OF PRODUCTION BUILDINGS IN HUMIDITY MODE (Spectrum Journal of Innovation, Reforms and Development, 2024)
The article deals with the effect of hydrophobizing additives on the thermophysical properties of expanded clay concrete.